The association between knowledge and cardiovascular risk in high school students in Bali Indonesia - Preiffer Agus Prasojo; Yohana Helenora Desy Lopez; Christianus Heru Setiawan (Pharmaciana, 2022)
Cardiovascular disease is one of the health problems that cause significant health, economic, and social burdens. Generally, cardiovascular disease starts to appear clinically at the age of 40 years and over. Currently, diabetes can appear early because of an unhealthy lifestyle since childhood. Senior high school students, the nation's next generation, are essential assets for the country. The school-age intervention is expected to increase student awareness for anticipating cardiovascular disease. This study focused on evaluating the relationship between the level of knowledge related to cardiovascular disease and the risk of cardiovascular disease in high school students. This study is an analytic observational with a cross-sectional design with purposive sampling. The instruments used in this study to measure the level of knowledge and cardiovascular risk are a closed-ended questionnaire, digital sphygmomanometer, scale, height meter, body measuring tape, and blood glucose self-test device. The total study population was 207 students from two senior high schools in Bali. Almost one-third of the subjects have high blood pressure. Nearly a quarter of the subjects are overweight-obese and have waist circumference above normal. The result showed no significant difference relationship between the level of knowledge and cardiovascular risk (P >0.05). Therefore, further education is needed to instil healthy behaviors to control cardiovascular risk factors as early as possible. In conclusion, there is no relationship between the level of knowledge on cardiovascular risk in two senior high schools in Bali.